Study of Traded Birds in Pontianak City and Kubu Raya Regency, West Kalimantan Indonesia - Nita Nurjanah; Fachruddin Majeri Mangunjaya; Tatang Mitra Setia; Anang Aditiya; M Syukur Wahyu Putra (Universitas Nasional Jakarta, 2021)
Birds are animals that are very closely related to human life, both to be used as food or to be distributed as a hobby. However, at this time the existence of birds in nature is increasingly experiencing a decline in diversity and is even threatened with extinction. The purpose of this study was to determine the types of birds traded in the city of Pontianak and Kubu Raya regency along with their IUCN status and trade status (CITES). This research was conducted in March-April 2021. The method used was direct observation (recording) and conducting interviews with bird shop owners. The data obtained were analyzed using qualitative descriptive analysis. Based on the results of research that has been done, the number of shops in Pontianak Cityis19 bird shops. Meanwhile, the number of shops in Kubu Raya Regencyis nine bird shops. The most common birds found in stores are from the Muscicapidae family, 48 species of birds traded with least concern (LC) status, five species of near threatened (NT), eight species of vulnerable (VU), and two species of critically endangered (CR). 58 bird species are not included in the CITES appendix list, one species is included in Appendix I, namely Zosterops palpebrosus, and four species are included in Appendix II, namely Leucopsar rothschildi, Garrulax canorus, Pycnonotus zeylanicus, and Melopsittacus undulates. Meanwhile, the majority of the birds (91%) found in the stores come from the wild compared to those from livestock (9%). The results also showed that wild birds were obtained by traders through hunting and buying from others.